INFLUENCE OF SOCIAL MEDIA MARKETING, ELECTRONIC WORD OF MOUTH AND CONSUMER ENGAGEMENT TO BRAND LOYALTY IN INDONESIA GRAB COMPANY - Bismoaziiz; Usep Suhud; Saparuddin (The Institute of Academic Research and Publication (IARP), 2021)
This study aims to analyze social media marketing, electronic word of mouth, and consumer attachment to brand loyalty in Grab Indonesia. The research design used is quantitative research with a causal approach that examines the effect of exogenous variables (social media marketing, electronic word of mouth, and consumer attachment) on endogenous variables (brand loyalty). The population in this study were consumers of social media followers (Instagram) grab with an infinite number, therefore sampling was carried out using purposive sampling with the consideration of respondents as followers of Instagram grab with a minimum period of following is 6 months and has given